Essential Trace and Toxic Element Distribution in the Scalp Hair of Pakistani Myocardial Infarction Patients and Controls - Afridi, Hasssan Imaran; Kazi, Tasneem Gul; Kazi, Gul Hassan; Jamali, Mohammad Khan; Shar, Ghulam Qadir (Biological trace element research, 2006)
The pathogenesis of heart disease has been associated with changes in the balance of certain trace elements. The aim of this study was to evaluate the Zn, Fe, Cu, Cr, Ni, Pb, and Cd contents in scalp hair samples of myocardial infarction (MCI) patients hospitalized in the cardiac ward of National Hospital in Hyderabad city (Pakistan). Scalp hair samples were collected from 193 patients (104 male, 89 female) of 3 age groups (46-60, 61-75, and 76-90 yr), for a comparative study, 200 normal, healthy subjects (103 male, 97 female) of the same age groups residing in the same city were selected. All metals in scalp hair samples were assessed by a flame/ graphite furnace atomic absorption spectrophotometer, prior to microwave-assisted and conventional wet acid digestion methods. Results were calculated in micrograms per gram. The mean values of Fe and Zn of scalp hair samples of MCI patients were significantly reduced compared to the control subjects of both genders. The mean Fe concentrations in male patients were 19.42, 12.36, and 6.98 vs 30.69, 24.42, and 16.75 for the control patients in the three age groups (46-60, 61-75, and 76-90 yrs, respectively). The mean Zn concentration in male patients were 169.2, 149.4, and 107.7 microg/g vs 206.1, 188.0, and 154.4 microg/g for the control group (p < 0.002, 0.004, and 0.001) in all three age groups, respectively. These differences were also observed in the female study groups. The mean values of Pb, Cd, and Ni were significantly high in patients compared to healthy subjects (mean Pb in male patients: 11.85, 12.89, and 14.52 those of female patients were 11.88, 12.73, and 14.21 vs the male controls patients (6.08, 7.56, and 8.56) and female controls (5.99, 7.41, and 8.25) for all three age groups, respectively. The concentration of Ni and Cd in the scalp hair samples of the heart patients of both sexes were significantly higher compared to the control; in the case of Ni the range of significant difference for males was found to be p < 0.001-0.009 and for females to be p < 0.0.002-0.007 and significantly high concentration of Cd were observed in hair samples of patients than in controls in the range for males (p < 0.001-0.009) and in females (p < 0.001-0.011). The Zn/Cu and Zn/Cd ratios in the scalp hair (p < 0.01) of the diseased groups were significantly lower than that of the healthy groups. Deficiency of essential trace metals and high level of toxic metals might play a role in the development of heart disease in the subjects of this study. Toxic metals might also cause diminished absorption of essential elements.